Concepts of ferrovalley material and anomalous valley Hall effect - Wen-Yi Tong (Nature Portfolio, 2016)
Spontaneous polarization leads to various functionalities promising for future information storage and electronics. Here, the authors propose the concept of ferrovalley material with spontaneous valley polarization in monolayer 2H-VSe2.